Preparo psicológico para o tratamento odontológico em crianças: estudo clínico randomizado - Pelizzoni, Aline Vaneli (2020)
This is a randomized clinical study with the objective of evaluating psychological preparation as a possible toll to monimize the anxiety between children and their parents. The research was based on the fundamentals of Historical-Cultural Psychology and quantitative and qualitative. The study sample consisted of children aged eight and nine, who were waiting for care at the pediatric dentistry clinic with their parentes and or guardians. All children analyzed underwent the same type of prophylaxis procedure. The sample was randomized in a control group (CG), which received the routine treatment of the referred clinic (talk-show-do), which corresponds to the individuals who received psychological preparation prior to the dental procedure. The research was carried out in two stages, first the quantitative data were collected through the CORAH Dental Anxiety Scale applied to parents and/or guardians and, the Children’s Fear Survey Schedule-Dental Subscale Scale to assess fear and anxiety in children. These questionnaires were used before and after the procedure, featuring pre-test and post-test. The psychological preparation consisted of the presentation and interaction with the dental instruments and materials, as well as the clinic environment, using the Instructional Therapeutic Toy (ITT) technique. Qualitative information was extracted from the processo f leading children with ITT, which was recorded in a field diary for content analysis of the thematic unit of meaning. The statistical analysis of the data was performed using the SPSS IBM® software version 20.0. For all analyzes, the level of significance was set at 95% and p<0,05. The Shapiro-Wilk test found normality in the data. Descriptive statistics related the mean, standard deviation, 95% confidence interval and values of used to verify the difference between the pre and post test moments in bith groups, but no statistical significance was found between CG and IG. The t-test for paired samples was used to verify the difference between anxiety scores in the pre and post-intervention moments that showed a reduction in anxiety and fear levels fot both groups. Pearson’s correlation test showed that there is no relationship between the levels of anxiety and fear between parents and children. The thematic analysis of significance demonstraded a new meaning in oral health care.